Influence of water-controlled release process on the physical and chemical property of nanosize TiO2 particles. (22nd March 2019) - Gao, Xiaorong; Chang, Honghong; Asakura, Yusuke; Zhao, Zhihuan; Gao, Wenchao; Qiao, Yan; Yin, Shu
Abstract: The water-controlled release process (WCRP) was utilized for the synthesis of TiO2 photocatalyst. The effect of alkylated esterified WCRP system on the morphology, specific surface area (SSA) and photocatalytic activity of TiO2 were studied systematically. By changing the structure of alcohol and acid involved in the esterification reaction, we found that the SSA and photocatalytic activity of TiO2 obtained in an ethanol/acetic acid reaction mixture showed the best results. Interestingly, the TiO2 obtained in t -butanol/acetic acid contains both the anatase and rutile phase, while the other systems only possessed anatase phases. The conditions of ethanol and acetic acid esterification were optimized and the experimental results showed that the SSA of nano-TiO2 was improved by shorting the reaction time or adding an organic solvent, which can form an azeotrope with water, but no effect on the photocatalytic activity could be observed. The reaction mechanism of esterified WCRP system was furthermore studied by NMR spectroscopy, showing three kinds of reaction, namely esterification, etherification and hydrolysis.